Implementasi Sistem Bagi Hasil pada Ekowisata Sawah BUMDesa Pematang Johar: Tinjauan PP No. 11/2021 dan Perspektif Fikih Muamalah Wahbаh Az-Zuhaili - Rahman Maulana Harahap; Imam Yazid (Institut Agama Islam Sultan Muhammad Syafiuddin Sambas, 2026)
The profit-sharing system is one of the cooperation mechanisms implemented in the management of Village-Owned Enterprises (Badan Usaha Milik Desa—BUMDes) to promote community welfare. However, Government Regulation Number 11 of 2021 concerning Village-Owned Enterprises does not specifically regulate the technical mechanism of profit-sharing, potentially creating legal uncertainty. This study aims to analyze the legal framework of profit-sharing under Government Regulation Number 11 of 2021, examine its implementation in the Rice Field Ecotourism Unit of BUMDes Pematang Johar, and evaluate its conformity with the principles of fiqh muamalah from the perspective of Wahbah Az-Zuhaili. This research employs a legal research method using the statute approach and conceptual approach, supported by field research through observation, interviews, and document analysis. The data were analyzed using a qualitative descriptive method. The findings indicate that Government Regulation Number 11 of 2021 provides a legal basis for BUMDes but does not regulate the technical aspects of profit-sharing. The existing practice in the Rice Field Ecotourism Unit of BUMDes Pematang Johar relies mainly on oral agreements, resulting in uncertainty regarding profit-sharing ratios, risk allocation, and the rights and obligations of the parties. Therefore, a written agreement is required to ensure legal certainty and compliance with the principles of fiqh muamalah.